Efficacy of Bacillus subtilis for the control of Pseudomonas syringae pv. actinidiae under field conditions - Vaz, António Trindade (2018)
Bacterial canker of kiwifruit, caused by Pseudomonas syringae pv. actinidiae (Psa), is a disease included on the EPPO A2 List because it is currently increasing in the Mediterranean region. Climatic conditions determine the multiplication and dispersal behavior of Psa and may influence its biological control (BC). However, information regarding the influence of climatic conditions on growth of the Psa bacterium in Portugal is scarce. The aims of this study were to relate the climatic conditions with the efficacy of Bacillus subtilis Serenade Max® in controlling the disease, to determine whether disease incidence increased over the growing season, and to monitor carry-over of disease from one season to the next. Two ‘Hayward’ orchards of Actinidia deliciosa of different ages, located in Valença, in the north of Portugal, were selected for BC assay. Thirty plants were randomly selected from a young orchard (6 years old) and another 30 plants from an old one (30 years old). Psa was identified and characterized by morphological, biochemical and molecular tests. The efficacy of B. subtilis was evaluated by disease incidence, and correlated to climatic conditions. A standardized leaf infection index (0-4 scale of symptoms) was used to determine disease severity. Monitoring of Psa symptoms was performed every 30 days, from June 2016 to April 2017. The severity of the disease decreased in the summer season, characterized by unfavorable conditions for Psa such as high temperatures and scarce precipitation. B. subtilis was partially effective in controlling Psa in the 6-year-old orchard, and showed no efficacy in the protection of leaves in the 30-year-old orchard. B. subtilis applied at flowering could be considered as a suitable solution for the control of Psa biovar 3 only for the new kiwifruit orchard (6 years old).